Cobalt Oxide Nanoparticles: Behavior towards Intact and Impaired Human Skin and Keratinocytes Toxicity - Mauro, Marcella; Crosera, Matteo; Pelin, Marco; Florio, Chiara; Bellomo, Francesca; Adami, Gianpiero; Apostoli, Piero; De Palma, Giuseppe; Bovenzi, Massimo; Campanini, Marco; Filon, Francesca (International journal of environmental research and public health, 2015)
Skin absorption and toxicity on keratinocytes of cobalt oxide nanoparticles (Co3O4NPs) have been investigated. Co3O4NPs are commonly used in industrial products and biomedicine. There is evidence that these nanoparticles can cause membrane damage and genotoxicity in vitro, but no data are available on their skin absorption and cytotoxicity on keratinocytes. Two independent 24 h in vitro experiments were performed using Franz diffusion cells, using intact (experiment 1) and needle-abraded human skin (experiment 2). Co3O4NPs at a concentration of 1000 mg/L in physiological solution were used as donor phase. Cobalt content was evaluated by Inductively Coupled–Mass Spectroscopy. Co permeation through the skin was demonstrated after 24 h only when damaged skin protocol was used (57 ± 38 ng·cm−2), while no significant differences were shown between blank cells (0.92 ± 0.03 ng cm−2) and those with intact skin (1.08 ± 0.20 ng·cm−2). To further investigate Co3O4NPs toxicity, human-derived HaCaT keratinocytes were exposed to Co3O4NPs and cytotoxicity evaluated by MTT, Alamarblue® and propidium iodide (PI) uptake assays. The results indicate that a long exposure time (i.e., seven days) was necessary to induce a concentration-dependent cell viability reduction (EC50 values: 1.3 × 10−4 M, 95% CL = 0.8–1.9 × 10−4 M, MTT essay; 3.7 × 10−5 M, 95% CI = 2.2–6.1 × 10−5 M, AlamarBlue® assay) that seems to be associated to necrotic events (EC50 value: 1.3 × 10−4 M, 95% CL = 0.9–1.9 × 10−4 M, PI assay). This study demonstrated that Co3O4NPs can penetrate only damaged skin and is cytotoxic for HaCat cells after long term exposure.